2015
DOI: 10.11646/phytotaxa.233.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and phylogeny of Cercospora spp. from Northern Thailand

Abstract: The genus Cercospora represents a group of important plant pathogenic fungi with a wide geographic distribution, being commonly associated with leaf spots on a broad range of plant hosts. The goal of the present study was to conduct a morphological and molecular phylogenetic analysis of the Cercospora spp. occurring on various plants growing in Northern Thailand, an area with a tropical savannah climate, and a rich diversity of vascular plants. Sixty Cercospora isolates were collected from 29 host species (rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Notes : Nguanhom et al . (2015) examined Cercospora species from northern Thailand by means of molecular methods.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Notes : Nguanhom et al . (2015) examined Cercospora species from northern Thailand by means of molecular methods.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…With DNA sequencing becoming widely available for use by mycologists as a reliable source of information ( Taylor et al 2000 ), a more concrete classification of fungi was initiated, and several studies have since been published on cercosporoid fungi ( Arzanlou et al 2007 , Crous et al 2007a , 2009b , d , 2013a , Braun et al 2013 , Groenewald et al 2013 , Bakhshi et al 2014 , 2015 , Nguanhom et al 2015 ). These studies have shown that some morphology-based genera were largely monophyletic, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An NCBI BLASTn search for ITS sequence similarity was done with the type database of NCBI (Altschul et al 1990 ). Based on the closest similarity of the BLASTn search, the ITS region sequences of ex-type and authentic strains, sequences from Groenewald et al ( 2013 ), and Nguanhom et al ( 2015 ) were retrieved from GenBank. Alignment of sequences was done using Clustal W of Molecular Evolutionary Genetics Analysis (MEGA) software v 7.0 (Kumar et al 2016 ).…”
Section: Ima Genome-f 13bmentioning
confidence: 99%